Kafka's Zoopoetics : Beyond the Human-Animal Barrier - Harel, Naama, 1973- (Book collections on Project MUSE., 2020)
"Kafka's Zoopoetics is the first extensive account of animals and human-animal relations in the work of Franz Kafka. The book appeals to a broad audience, including scholars and students of Comparative Literature, German Studies, Cultural Studies, and Human-Animal Studies. Kafka's pivotal role in world literature cannot be overestimated. Exploring the multidimensional relations between humans and animals, the rapidly growing interdisciplinary field of Human-Animal Studies intertwines political and environmental critical paradigms, which are at the core of the contemporary intellectual discussion"--